Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-OTO - Díaz-Lorca, Anna; Morales-Nin, Beatriz (2021)
[EN] IMEDEA-OTO includes more than 300 lots of Actinopterygian fish otoliths, with a total of approximately 43,000 samples, from the Mediterranean Institute for Advanced Studies (CSIC-UIB) thanks to the different campaigns led by Dr. Beatriz Morales-Nin. The samples come mainly from the Mediterranean Sea, the Antarctic Ocean and the Atlantic Ocean.There are representations of 157 species and 52 different families. The most represented orders are Perciformes, Gadiformes, Scorpaeniformes, Salmoniformes, respectively.The otoliths are whole or in dry preservation. The collection continues to grow. [ES] IMEDEA-OTO incluye más de 300 lotes de otolitos de peces Actinopterigios, con un total aproximado de 43.000 muestras, del Instituto Mediterráneo de Estudios Avanzados (CSIC-UIB) gracias a las diferentes campañas lideradas por la Dra. Beatriz Morales-Nin. Las muestras proceden básicamente del mar Mediterráneo, del océano Antártico y del océano Atlántico. Hay representación de 157 especies y 52 familias diferentes. Los órdenes más representados son Perciformes, Gadiformes, Scorpaeniformes, Salmoniformes, respectivamente. Los otolitos se encuentran enteros o en preparación, todos conservados en seco. La colección sigue en crecimiento.